1997
DOI: 10.1001/jama.1997.03550030074038
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sepsis Syndrome in 8 Academic Medical Centers

Abstract: Sepsis syndrome is common in academic hospitals, although the overall rates vary considerably with the patient population. A substantial fraction of cases occur outside ICUs. An understanding of the hospitalwide epidemiology of sepsis syndrome is vital for rational planning and treatment of hospitalized patients with sepsis syndrome, especially as new and expensive therapeutic agents become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
224
4
10

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(247 citation statements)
references
References 22 publications
9
224
4
10
Order By: Relevance
“…The other studies reported a higher prevalence of sepsis in patients aged 57 years. 12 We found a slightly higher percentage of males affected with sepsis compared to females in the present study. Other studies also indicated a higher incidence in male.…”
Section: Discussioncontrasting
confidence: 45%
“…The other studies reported a higher prevalence of sepsis in patients aged 57 years. 12 We found a slightly higher percentage of males affected with sepsis compared to females in the present study. Other studies also indicated a higher incidence in male.…”
Section: Discussioncontrasting
confidence: 45%
“…It is an infection-initiated systemic inflammatory reaction syndrome resulting from the interactions between environmental and genetic factors. [1][2][3] Septic shock, the most severe complication of sepsis, is a deadly disease. Many mechanisms are involved in the pathophysiology of septic shock, including the release of cytokines, the activation of neutrophils, monocytes, and microvascular endothelial cells, as well as the activation of neuroendocrine reflex and plasma protein cascade systems (complement system, the intrinsic and extrinsic pathways of coagulation, and the fibrinolytic system).…”
Section: Introductionmentioning
confidence: 99%
“…1 This mortality increases when multiple organ and systemic dysfunctions occur. Although not having a wellelucidated pathogeny, this dysfunction seems to be consequent to a complex inflammatory process.…”
Section: Introductionmentioning
confidence: 99%